Specyfika struktury i poziomu konsumpcji w gospodarstwach domowych rodzin niepełnych biologicznie - Gutkowska, Krystyna; Wiśniorowska-Gieras, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2002)
Single parents families are specific in terms of the social and economic characteristics. Both an analysis of individual data on household budgets and different cross-cultural studies suggest that any differences between families with both parents and with single parent are determined by their economic situation as well as by social and psychical conditions. Therefore, we observe differences between those families with respect to the structure and the level of consumption especially when single mother families are taken into consideration.